Disruptive Effects of Colorful vs. Non-colorful Play Area on Structured Play—A Pilot Study with Preschoolers - Stern-Ellran, Keren; Zilcha-Mano, Sigal; Sebba, Rachel; Levit Binnun, Nava (Frontiers in Psychology, 2016)
To contribute to young children's development, sensory enrichment is often provided via colorful play areas. However, little is known about the effects of colorful environments on children while they engage in age-appropriate tasks and games. Studies in adults suggest that aspects of color can distract attention and impair performance, and children are known to have less developed attentional and executive abilities than adults. Preliminary studies conducted in children aged 5-8 suggest that the colorfulness of both distal (e.g., wall decorations) and proximal (e.g., the surface of the desktop) environments can have a disruptive effect on children's performance. The present research seeks to extend the previous studies to an even younger age group and focus on proximal colorfulness. With a sample of 15 pre-schoolers (3-4 years old) we examined whether a colorful play surface compared to a non-colorful (white) play surface would affect engagement in developmentally appropriate structured play. Our pilot findings suggest that a colorful play surface interfered with preschoolers' structured play, inducing more behaviors indicating disruption in task execution compared with a non-colorful play surface. The implications of the current study for practice and further research are discussed.